An Islamic Reading of Moral Issues in Malay Novels - Mohamed Nor, Nora (2006)
This thesis centers on reading modern Malay literature as a site for understanding the Malay dilemma in upholding their religious beliefs against both traditional cultural beliefs and modernization brought about by westernization. Using a sociological approach within an Islamic framework, the study investigates how the Malay authors depict Malay characters who transgress Islamic teachings. The analysis particularly follows the guidelines of the three Islamic principles: Belief, Law and Moral Conduct. At the same time, it explores the social struggles of the Malays with morality within the contexts of themes such as poverty, pervasive folk culture, religious conservatism, unscrupulous middlemen and irresponsible leadership. The works selected are English translated works originally written by A. Samad Said, Shahnon Ahmad and Khadijah Hashim. The three authors are representative writers of their time who are considered to have applied their creativity to foreground Malay as a resilient ethnic group in the face of adversity and social struggles. The research suggests that Malay characters in the selected novels represent Malays who have an increasing lack of knowledge in Islam, leading readers to understand that Malay Muslims have mostly transgressed the Islamic teachings. This may due to the fusion between culture and religion in traditional Malay society, and is mirrored by the emergence of modern hybrid values practiced by contemporary Malay society in the advent of westernization and in the face of hardship. Thus, studies on modern Malay literature which use the Islamic approach give a better picture of Malay social and religious struggles.